Prediction of maximum probable strong ground motion in Singapore due to Sumatra earthquakes - Pan, Tso Chien (2008)
This report presents a methodology, which is applied to estimate the maximum probable ground motions in Singapore. The report starts with a brief review of the past historical earthquakes together with a detail description of the Bengkulu earthquake of 4 June 2000 that were felt Singapore. Then, ground motion simulation is applied and the worst-case scenario earthquake for Singapore is identified based on seismogram synthesis of various potential earthquakes in the Sumatra region that might affect Singapore.